ANALISIS FAKTOR YANG MEMPENGARUHI PEMAKAIAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) - Aisyah Aisyah; Ni Made Dewi Susanti; Yessy Arisman; Eni Nuraeni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The maternal mortality rate (MMR) in Indonesia is still relatively high compared to other countries, especially in Southeast Asia. One of the main causes of maternal mortality is bleeding during childbirth. Long-acting reversible contraception (LARC) is a highly effective method of contraception. The purpose of this study was to analyze the factors that influence the use of long-acting contraception (LARC). The research design used in this study was cross-sectional. The research was conducted in the working area of the Karang Tinggi Community Health Center. The research was conducted in May 2025. The research population was all acceptors recorded in the family planning register in the working area of the Karang Tinggi Community Health Center. The research sample consisted of 80 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between age (p value: 0.000) and parity (p value: 0.001) with the choice of contraceptive method. It is recommended that the Community Health Center improve its services, especially counseling on long-term contraceptive methods, in order to reduce the birth rate and improve maternal welfare. Keywords: MKJP, Parity, Age.